MOTIVASI INDONESIA MELAKUKAN DIPLOMASI BUDAYA MELALUI KAMPANYE WONDERFUL INDONESIA DI AZERBAIJAN TAHUN 2016-2017 - Okta Verina Cindy; Idjang Tjarsono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This paper aims to analyze cultural diplomacy, that explain about Indonesia’s desire for improve cooperation with Azerbaijan through Wonderful Indonesia in 2016 and 2017 in Baku, Azerbaijan. Cultural diplomacy is a category of soft diplomacy in the implementation of a country’s foreign policy. Cultural instruments used by Indonesia in the implementation of diplomacy through Indonesian Cultural Festival can reflect situation and diversity of Indonesian culture.This study uses neorealist perspectives by Kenneth Waltz, the analysis unit of the nation state and uses the theory of diplomacy by S.L Roy and supported by the concept of cultural diplomacy by Tulus Warsito and Wahyuni Kartikasari.This research shows that the Indonesian Cultural Festival stole the attention of many Azerbaijans and middle Asian citizens, seen from the number of visitors or viewers who reaced thousands of people and continue to increase every year. Increased knowledge and interest about indonesian culture are expected can attract Azerbaijan citizen to visit Indonesia. Implemented the culture diplomacy through this festival be expected can increase cooperation between Indonesia and Azerbaijan in tourism and sociocultural and also in several other field.Keywords: Cultural Diplomacy, Wonderful Indonesia, Indonesia-Azerbaijan relations